Radiological evaluation of ovarian mass by contrast-enhanced computed tomography abdomen with clinicopathological correlation in Eastern Indian population - Saha, Dona; Bhadra, Ram Chandra; Biswas, Nabonita (Asian Journal of Medical Sciences, 2022)
Background: Adenexal masses present diagnostic challenges. After identification of the ovarian mass, the most critical step is to determine the degree of suspicion for malignancy. It is mainly based on imaging modalities and clinicopathological correlation. Aims and Objectives: This radiological study was designed to differentiate benign and malignant ovarian masses by contrast enhanced-computed tomography (CECT) of abdomen and correlation of the radiological findings with histopathological report. Materials and Methods: This was a hospital-based prospective study conducted in Department of Radiodiagnosis, Nilratan Sircar Medical College and Hospital, Kolkata during January 2019–June 2020. The study was done on clinically suspected 50 patients of 15–50 years with ovarian mass having CECT diagnosed solid/complex solid cystic mass. Results: Among 50 cases under study, 37(74.0%) were benign which was significantly higher than that of malignant cases (26.0%). Malignancy was significantly associated with wall irregularity, solid-cystic composition, presence of thick septations, septal enhancement, presence of both septal, and solid enhancement pattern in CECT. Conclusion: Based on the results of the present study, multi-detector contrast-enhanced CT could be a rapid non-invasive and cost-effective step in the evaluation of ovarian masses.